2013
DOI: 10.1007/s11033-013-2603-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of microRNA-21 in regulating 3T3-L1 adipocyte differentiation and adiponectin expression

Abstract: MicroRNAs are endogenous small RNAs with a high degree of conservation, participating in a variety of vital activities. In present study, to explore the effect of microRNAs on 3T3-L1 adipocyte differentiation and adiponectin expression, the adipo-related microRNAs were screened and identified by micorRNA microarray. The highly expression plasmid of microRNA-21 with obvious expression up-regulation (miR-21) and its anti-sense (miR-21 inhibitor) were constructed and transfected into 3T3-L1 preadipocytes. The eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 29 publications
1
41
0
Order By: Relevance
“…Research in the field describes the regulation of miRNAs by adiponectin (11) or the regulation of adiponectin receptor expression by miRNAs (12,13). In murine cells, miR-21 and miR-378 have been reported to regulate adiponectin expression (14,15). Our results thus add an additional regulatory layer, namely the regulation of adiponectin itself by miRNA in human adipocytes.…”
Section: Discussionmentioning
confidence: 64%
“…Research in the field describes the regulation of miRNAs by adiponectin (11) or the regulation of adiponectin receptor expression by miRNAs (12,13). In murine cells, miR-21 and miR-378 have been reported to regulate adiponectin expression (14,15). Our results thus add an additional regulatory layer, namely the regulation of adiponectin itself by miRNA in human adipocytes.…”
Section: Discussionmentioning
confidence: 64%
“…In this regard, it is interesting to note that circulating levels of miR-21 are increased in human patients with NAFLD43 which may potentially impact the adipose tissue physiology. Indeed, recent studies reported a role for miR-21 in adipocyte differentiation 67 68. Whether circulating miR-21 may promote IR and glucose intolerance in muscle or adipose tissue, thereby explaining the increased glucose tolerance observed in LImi21RKO mice fed an HFD, is currently unknown and under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Although pivotal transcription factors involved in Adipoq expression have been previously identified [6], the mechanisms for Adipoq regulation remain obscure. There are reports showing an association between miRNA and adiponectin [19], [20], but there are only few reports investigating the possibility that miRNAs could directly regulate Adipoq transcription [21]. We sought putative target sites for miRNAs in the 3'UTR of the adiponectin gene using TargetScan and PicTar and found that miRNA-378 could directly target the 3'UTR of adiponectin.…”
Section: Discussionmentioning
confidence: 99%